A telemedicine communication exchange network in Gorno-Badakhshan Autonomic Oblast in collaboration with Swiss Surgical Teams. (August 2022) - Mamadnabiev, Intizor; Imfeld, Stephan; Gürke, Lorenz; Aschwanden, Markus; Isaak, Andrej
Introduction: The purpose of this article is to report on the implementation of a telemedicine network serving as a second opinion pool for a surgeon in a remote area of a developing country. Methods: This study involved an international collaboration between two members of Swiss Surgical Teams at a tertiary referral hospital and a surgeon in a remote area in Gorno-Badakhshan Autonomic Oblast, Tajikistan, which established a second opinion pool discussing diagnostics and therapeutic options via a messenger application. A retrospective analysis of response times was performed using a series of 50 challenging cases. Results: The median time to receive a first telemedical response from any of the two contacts was 24 min (interquartile range 6–73). Urgent and emergent pathologies accounted for 57% of cases. The suggested treatment was carried out in 90% ( n = 44) of cases. Conclusions: Timely and convenient telemedicine support to provide diagnostic and therapeutic reassurance and improve treatment quality for patients presenting to a general and vascular surgeon in the large and remote region of Gorno-Badakhshan Autonomic Oblast can be installed via a messenger application.